To make men free - Kelly, Frank K.
In To Make Men Free, celebrated historian Heather Cox Richardson traces the shifting ideology of the Grand Old Party from the antebellum era to the Great Recession, revealing the insidious cycle of boom and bust that has characterized the Party since its inception. While in office, progressive Republicans like Teddy Roosevelt and Dwight Eisenhower revived Lincoln's vision of economic freedom and expanded the government, attacking the concentration of wealth and nurturing upward mobility. But they and others like them have been continually thwarted by powerful business interests in the Party. Their opponents appealed to Americans' latent racism and xenophobia to regain political power, linking taxation and regulation to redistribution and socialism. The results of the Party's wholesale embrace of big business are all too familiar: financial collapses like the Panic of 1893, the Great Depression in 1929, and the Great Recession in 2008. With each passing decade, with each missed opportunity and political misstep, the schism within the Republican Party has grown wider, pulling the GOP ever further from its founding principles. Expansive and authoritative, To Make Men Free is a sweeping history of the Party that was once America's greatest political hope--and, time and time again, has proved its greatest disappointment.